Cross-group friendship and collective action in community solidarity initiatives with displaced people and resident/nationals - Vine, Megan; Greenwood, Ronni Michelle (Frontiers in Psychology, 2023)
Introduction: In Ireland, people seeking asylum (displaced people) receive accommodation in a system called “Direct Provision” (DP) while they wait for their applications for protection to be processed. The living conditions of DP have been described as illegal and inhumane by national and international human rights groups, and the system exacerbates the social exclusion of displaced people. Community responses to DP by displaced people and resident/nationals of Ireland include the creation of informal groups called community solidarity initiatives (CSI), through which cross-group friendships are forged by participation in shared cultural activities. We hypothesized that, compared to non-CSI participants, participants of CSI would report more cross-group friendships, and that more cross-group friendships would predict stronger collective action intentions to support the campaign to end DP, especially among resident/nationals. Methods: We recruited residents/nationals and displaced persons with and without CSI experience to complete a self-report questionnaire (n = 199), measuring cross-group friendship, collective action intentions, and intergroup attitudes. Data were collected between July 2020 and March 2021, using a combination of online and paper surveys. We conducted ANOVA and conditional process analyses on the data to test our hypotheses. Results: As predicted, CSI participants reported more contact with cross-group friends and stronger collective action intentions than non-participators. Conditional process analysis indicated that CSI participation facilitated resident/nationals’ political solidarity with displaced people through cross-group friendship. Discussion: Findings identify the role of group membership in the relationship between contact and collective action for migrant justice, illustrating the potential of CSI to bolster intergroup solidarity and social cohesion through shared activities and cross-group friendship. As such, findings make an important contribution to the literature on intergroup contact, solidarity, and social cohesion, and will be relevant for community practitioners, civil society organisations, NGOs, and policy makers.